Biotransformation and Detoxification of Antraquione Dye Green 3 using halophilic Hortaea sp. (May 2019) - Al Farraj, Dunia Abdulaziz; Elshikh, Mohamed Soliman; Al Khulaifi, Manal Mohammed; Hadibarata, Tony; Yuniarto, Adhi; Syafiuddin, Achmad
Abstract: The issue of dye disposal into the environment has received considerable critical attention. Therefore, this study aims to investigate the biodegradation and detoxification of Solvent Green 3 (SG3) by halophilic Hortaea sp. For toxicity examination, SG3 (before and after degradation) was inspected against two plants, which are Sorghum vulgare and Triticum aestivum . The maximum specific growth rate of the bacterium was 0.13 h −1 . The fastest duration for the complete removal of the dye and chemical oxygen demand was achieved at the lowest concentration of the dye. The presence of Cu 2+ performed a higher removal capability compared to other employed metal ions. The 1, 2-dioxygenase performed the highest enzymatic activity (up to 488 U/L). The 1, 2-dioxygenase and laccase were responsible for the biodegradation and detoxification of SG3. SG3 can be degraded by Hortaea sp. into lower toxicity compounds via two routes, which are initially transformed into 1, 4-diaminoanthracene-9, 10-dione and p-toluidine before degraded into phthalic acid and 4-hydroxybenzoic acid, respectively. The biodegraded product of SG3 achieved better the germination percentage, plumule, and radical lengths of the plants compared to SG3. In general, this study revealed that the dye can be completely removed by the bacterium and can be transformed into lower toxicity compounds. Highlights: Biotransformation and detoxification of SG3 using Hortaea sp. were investigated. Toxicity properties of SG3 and the degraded product were examined against plants. The dye and chemical oxygen demand can be completely removed by Hortaea sp. 1, 2-Dioxygenase and laccase were responsible for biodegradation of SG3. SG3 can be degraded by Hortaea sp. into lower toxicity compounds.